Walkability Beyond the Platform; Enhancing Multidisciplinary Planning Processes for Pedestrian Networks Around Station Areas Through Expert Insights and Resident Perspectives - Högberg, Klara; Sparlund, Johanna (My University, 2026)
Walking plays a central role in access to public transport, yet barriers in the built environment continue to limit pedestrian accessibility to station areas. While pre vious research has identified factors influencing walkability, less attention has been given to how these factors shape pedestrian behavior in the context of public trans port station areas. This study examines walkability and barrier effects in pedestrian access to public transport station areas, with a focus on Mölndal station. The aim is to understand which factors influence individuals’ willingness to walk to stations and to identify how multidisciplinary planning processes and governance can be im proved to enhance walkability and address barriers. A mixed-method approach was applied. Data were collected through expert interviews with planners from various organizations, a web-based survey targeting travelers in the area, site audits, and spatial mapping of perceived hindrances. The survey data were further analyzed us ing binomial logistic regression to identify relationships between perceived walking conditions and barrier effects. The result reveals a mismatch between planners’ and users’ perceptions of walkability. While professionals emphasize directness in pedes trian networks, users place greater importance on short distances and the quality of walking paths. Regression analysis shows that factors such as good lighting reduce the probability of avoiding routes or choosing alternative stations. The findings also highlight spatial differences in barrier types and demonstrate that walkability is shaped by the interaction between environmental conditions and individual abili ties. From a governance perspective, the study identifies fragmented responsibilities and insufficient integration of user perspectives as key challenges in multidisciplinary planning processes. These issues can result in suboptimal solutions and discontinu ities in the pedestrian environment. The study concludes that improving walkability requires a holistic and user-centered planning approach that combines quantitative and qualitative data. Barrier effects should be understood as multidimensional and context-dependent, emerging from the interaction of infrastructure, perception, and human capabilities. At the same time, the pedestrian journey needs to be treated as a seamless whole, which requires improved collaboration across actors to ensure continuous and well-integrated routes, where the interfaces become unnoticeable to pedestrians. Strengthened collaboration, clearer responsibility distribution, and in creased use of qualitative user data are essential for creating accessible and coherent pedestrian networks around station areas.
Keywords: walkability, Mölndal station, pedestrian accessibility, public transport stations, infrastructural barriers, barrier effects, governance, multidisciplinary plan ning, walking environment, binomial logistic regression analysis